Sexual activity and cardiovascular disease - Sosa Rosado, José Manuel (2012)
The prevalence of non transmissible chronic diseases is increasing among us either because of longer life expectancy of the population or because of the acquisition of unhealthy lifestyles. This goes along with an increase in the prevalence of obesity, arterial hypertension and diabetes, as well as higher incidence in coronary events in young patients. So that restart of sexual activity following a coronary event and use of phosphodiesterase inhibitors are themes that we need to discuss more frequently with our patients and their spouses. This has a positive effect in mental health and quality of life of our patients. In this article the most frequent asked questions that we need to solve as cardiologists with our patients are discussed.